ABS (Acrylonitrile Butadiene Styrene) composition with long-term plugging resistance as well as preparation method and application of ABS composition

By combining SAN resin and ABS toughening agent, and introducing PET resin and phase change microcapsules, the shortcomings of existing ABS compositions in toughness and long-term plug-and-resistance performance are solved, and the ABS composition with high toughness, good mechanical properties and plug-and-resistance performance is achieved, which is suitable for the preparation of building block toys.

CN119570170AActive Publication Date: 2025-03-07KINGFA SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411716115.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing ABS compositions fail to have both toughness and long-term plug-and-removal resistance, making it difficult to meet the high requirements of building block toys for dimensional stability and long-term plug-and-removal power.

Method used

By combining SAN resin and ABS toughening agent, introducing PET resin and compatible agent, and adding thermal conductivity and phase-transformation microcapsules at specific phase transition points, the ratio is regulated to improve the mechanical properties and thermal stability of the material.

Benefits of technology

The high toughness, good mechanical properties and long-term plug-and-removal resistance of ABS composition are achieved, which meets the requirements of dimensional stability and plug-and-removal force retention of building block toys, and at the same time improves the thermal stability and antibacterial properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156914850000021
    Figure BDA0005156914850000021
  • Figure BDA0005156914850000061
    Figure BDA0005156914850000061
  • Figure BDA0005156914850000071
    Figure BDA0005156914850000071
Patent Text Reader

Abstract

The invention discloses an ABS (Acrylonitrile Butadiene Styrene) composition with long-term plugging resistance as well as a preparation method and application thereof, and relates to the technical field of high polymer materials. The ABS composition comprises SAN (Styrene Acrylonitrile Butadiene Styrene) resin, an ABS flexibilizer, PET (Polyethylene Terephthalate) resin, a compatilizer, a heat conducting agent and a phase change microcapsule, the phase change point of the phase change microcapsule is 25-30 DEG C. According to the invention, the SAN resin and the ABS flexibilizer are compounded, the ratio is regulated and controlled, and the PET resin and the compatilizer are introduced, so that the ABS composition has good mechanical properties. Meanwhile, the heat conduction agent and the phase change microcapsule with a specific phase change point are introduced, so that the friction temperature rise amplitude of the material in the continuous insertion and extraction process can be reduced, the heat stability is improved, the insertion and extraction force retention rate of the material during long-term insertion and extraction is improved, and the material can be applied to building block toys to meet the requirement of long-term insertion and extraction resistance of building blocks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically to an ABS composition resistant to long-term plugging and unplugging, and a preparation method and application thereof. Background Art

[0002] Acrylonitrile-butadiene-styrene copolymer (ABS) resin has good mechanical properties, high-gloss aesthetic effects and excellent processing performance, and is widely used in various industries. Most of the toy industry uses ABS resin as the main material for product parts. For building block toys, people's requirements for long-term plug-in and pull-out performance retention are gradually increasing.

[0003] Polyethylene terephthalate (PET) is a crystalline saturated polyester with excellent physical and mechanical properties and resistance to organic solvents over a wide temperature range. It is widely used in various packaging containers and the textile industry. Most PET plastics are used in food-contact grade drinking water bottles and beverage bottles. The PCR-PET plastics obtained after recycling can meet the requirements of chemical control in the toy industry and are a potential material for reducing carbon emissions in the toy industry. However, PET has a very obvious disadvantage of slow crystallization rate, difficult injection molding, long production cycle, and average dimensional stability. Toy building blocks have very high requirements for dimensional stability and long-term plug-in and pull-out force, as well as high requirements for injection molding efficiency, and pure PET cannot meet this requirement. The ABS / PET alloy blended with ABS can improve the processability of injection molding and has good mechanical properties, but when used in building block products, it cannot meet the requirements of long-term plug-in resistance.

[0004] Patent CN114836002A proposes a high-toughness and high-magnetic attraction ABS alloy and its preparation method and application. ABS resin and polyester resin are compounded to obtain a high-toughness ABS alloy, which can be used in the preparation of household appliances and toys; however, it also fails to meet the requirements of long-term plug-in resistance and is not suitable for the preparation of building block products. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects and shortcomings of the existing ABS composition that it fails to have both toughness and long-term plug-in resistance, and to provide an ABS composition.

[0006] Another object of the present invention is to provide a method for preparing an ABS composition.

[0007] Another object of the present invention is to provide use of the above ABS composition in preparing building block toys.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] The present invention protects an ABS composition, comprising the following components in parts by weight:

[0010]

[0011] The phase change point of the phase change microcapsule is 25-30°C; the phase change point is tested by differential scanning calorimetry (DSC);

[0012] The intrinsic viscosity of the PET resin is 0.6-0.9 dL / g, and the test standard is GB / T 17931-2018.

[0013] In the ABS composition of the present invention, SAN resin and ABS toughening agent are compounded and the ratio is adjusted, and PET resin and compatibilizer are introduced at the same time, so that the ABS composition has good mechanical properties. The introduction of thermal conductive agent and phase change microcapsules with specific phase change points can reduce the friction temperature rise of the material during continuous plugging and unplugging, improve thermal stability, and thus improve the plug-in force retention rate of the material during long-term plug-in and unplugging; at the same time, PET resin with specific characteristic viscosity will migrate to the surface of the workpiece during the injection molding process, driving the phase change microcapsules to enrich on the surface of the workpiece, which is beneficial to improving the long-term plug-in resistance of the material, and can be applied to building block toys to meet the requirements of long-term plug-in resistance of building blocks.

[0014] In addition, controlling the intrinsic viscosity of PET resin is beneficial to improving toughness and improving the compatibility of the system. If the intrinsic viscosity is too low, the toughness will deteriorate and the notched impact strength will decrease significantly; if the intrinsic viscosity is too high, the compatibility with other materials will decrease, affecting the mechanical properties.

[0015] Phase change microcapsules are a type of energy storage (heat storage) material, which are microcapsules made of specific phase change materials through a coating process. When the external temperature changes, the state of the phase change material in the microcapsule changes, absorbing or releasing a large amount of latent heat. When the external temperature is higher than the phase change temperature point, the core material will actively absorb heat; when the external temperature is lower than the phase change temperature point, the microcapsule will release heat and keep its own temperature constant, thereby achieving the effect of alleviating thermal shock and intelligent temperature control.

[0016] The core materials of existing phase change microcapsules can be divided into solid-liquid, solid-gas, liquid-gas and solid-solid phase change materials. The present invention prefers solid-liquid phase change materials. Preferably, the phase change material of the phase change microcapsule of the present invention is paraffin and / or fatty acid. More preferably, the fatty acid is selected from butyl stearate.

[0017] The wall materials of existing phase change microcapsules are divided into natural polymer materials (such as chitosan, starch), synthetic polymer materials (such as acrylic urea-formaldehyde resin, melamine formaldehyde resin) and inorganic materials (such as silicon dioxide, calcium carbonate); preferably, the wall material of the phase change microcapsule of the present invention is selected from polymer materials with good high temperature stability, including but not limited to acrylic acid, polystyrene, urea-formaldehyde resin, melamine formaldehyde resin; more preferably, the capsule wall material of the phase change microcapsule of the present invention is melamine resin, and its heat resistance temperature is ≥260°C.

[0018] Preferably, the intrinsic viscosity of the PET resin is 0.6-0.8 dL / g; more preferably, the intrinsic viscosity of the PET resin is 0.6-0.7 dL / g.

[0019] In some embodiments, the SAN resin content that can achieve the purpose of the present invention can be 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, and 60 parts.

[0020] In some embodiments, the mass fraction of acrylonitrile (AN) monomer in the SAN resin is 22-28%, and the test method for acrylonitrile content is infrared spectroscopy. Using SAN resin with a specific AN content is beneficial to improving the compatibility of the system and making the material have good mechanical properties.

[0021] In some embodiments, the SAN resin has a melt mass flow rate of 20-40 g / 10 min at a temperature of 220° C. and a load of 10 kg, and the melt mass flow rate is measured according to ISO 1133 standard.

[0022] In some embodiments, the content of ABS toughening agent that can achieve the purpose of the present invention can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, and 27 parts.

[0023] In some embodiments, the mass fraction of butadiene monomer in the ABS toughening agent is above 60%, preferably 60-65%. The test method for the butadiene monomer content is infrared spectroscopy.

[0024] In some embodiments, the PET resin content that can achieve the purpose of the present invention can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, and 30 parts.

[0025] The PET resin can also be used as post-consumer recycled (PCR) PET plastic to achieve the purpose of the present invention. Preferably, the PCR plastic is PET recycled from food-grade PET plastic (such as drinking water bottles), which can solve the problem of lack of PCR solutions for ABS products in the toy industry and enable low-carbon sustainable development of the toy industry.

[0026] In some embodiments, the compatibilizer is styrene-acrylonitrile-glycidyl methacrylate and / or styrene-acrylonitrile-maleic anhydride copolymer.

[0027] In some embodiments, the thermal conductor is one or more of zinc oxide, magnesium oxide or aluminum oxide.

[0028] Preferably, the thermal conductor is zinc oxide and / or magnesium oxide; introducing an appropriate amount of the thermal conductor can not only improve the thermal conductivity of the composition, but also help to accelerate the crystallization rate of PET in the composition, improve the dimensional stability of the product and the injection molding processing efficiency, and at the same time, the thermal conductor can also inhibit the enrichment of bacteria on the surface of the material and improve the antibacterial properties of the material.

[0029] The present invention has no special requirements on the particle size of the thermal conductor; preferably, the particle size of the thermal conductor is 0.1 μm-50 μm.

[0030] In some embodiments, the ABS composition further comprises: 0.1-2 parts of an antioxidant and 0.1-2 parts of a lubricant.

[0031] Preferably, the antioxidant is a hindered phenol antioxidant and / or a phosphite antioxidant.

[0032] More preferably, the antioxidant is antioxidant 1010 and / or antioxidant 168.

[0033] Preferably, the lubricant is at least one of vinyl bisstearamide, polysiloxane, calcium stearate, magnesium stearate, zinc stearate, PE wax, and PP wax; preferably polysiloxane.

[0034] The invention protects a preparation method of an ABS composition, comprising the following steps: uniformly mixing various raw material components in a formula amount, melt-blending and extruding, and the processing temperature is 150-240° C. to obtain the ABS composition.

[0035] In some embodiments, the melt blending is performed using a twin-screw extruder or an internal mixer, with a processing temperature of 150° C. to 240° C. and a rotation speed of 50 rpm to 400 rpm.

[0036] When a twin-screw extruder is used for processing, the temperature of zones 1 and 2 is 120°C to 190°C, the temperature of zones 3 to 5 is 200°C to 240°C, the temperature of zones 5 to 10 is 200°C to 240°C, and the screw speed is 200rpm to 400rpm.

[0037] The present invention protects the use of an ABS composition in preparing building block toys.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention provides an ABS composition, wherein SAN resin and ABS toughening agent are compounded and the proportion is adjusted, and PET resin and compatibilizer are introduced at the same time, so that the ABS composition has good mechanical properties. The introduction of a thermal conductor and a phase change microcapsule with a specific phase change point can reduce the amplitude of friction temperature rise of the material during continuous plugging and unplugging, improve thermal stability, and thus improve the plug-in force retention rate of the material during long-term plug-in and unplugging; at the same time, the PET resin with a specific characteristic viscosity will migrate to the surface of the workpiece during the injection molding process, driving the phase change microcapsules to be enriched on the surface of the workpiece, which is beneficial to improving the long-term plug-in resistance of the material, and can be applied to building block toys to meet the requirements of long-term plug-in resistance of building blocks.

[0040] The notched impact strength of the ABS composition of the present invention is 13.8 KJ / m 2 The thermal conductivity is above 0.29W / (m*K), the plugging and unplugging force retention rate is above 84.6% after 30,000 times, and the 24-hour antibacterial rate is above 93.3%. It has excellent toughness, long-term plugging and unplugging resistance and antibacterial properties. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0042] The raw materials used in the following examples and comparative examples are as follows:

[0043] SAN resin 1#: SAN KFA-130, Liaoning Jinfa Technology Co., Ltd., AN content 25%.

[0044] SAN resin 2#: SAN SA30, LG Chemical (Huizhou) Chemical Co., Ltd., AN content 23%.

[0045] SAN resin 3#: SAN 300N H, Kumho Chemical Co., Ltd., South Korea, AN content 28%.

[0046] PET resin 1#: PET CR-7702, China Resources Chemical Technology Co., Ltd., intrinsic viscosity 0.5 dL / g.

[0047] PET resin 2#: PET FG718H, Sinopec Yizheng Chemical Fiber Co., Ltd., intrinsic viscosity 0.68 dL / g.

[0048] PET resin 3#: PET SY-G105, Wujiang Shuangyang Polyester Modifier Factory, intrinsic viscosity 1.1dL / g.

[0049] rPET 1#, derived from recycled drinking water bottles on land, has a characteristic viscosity of 0.65dL / g.

[0050] rPET 2#, derived from recycled drinking water bottles from the ocean, has an intrinsic viscosity of 0.61dL / g.

[0051] ABS toughening agent 1#: ABS high rubber powder, ABS POW HR181, Korea Kumho Chemical, butadiene content is 60wt%.

[0052] ABS toughening agent 2#: ABS high rubber powder, WD-133, Wanda Chemical Company, butadiene content is 65wt%.

[0053] Thermal conductor 1#: zinc oxide, D50 particle size is 5μm.

[0054] Thermal conductor 2#: magnesium oxide, modified ultrafine magnesium hydroxide (2500-GT), Yingkou Global Powder Engineering Co., Ltd., D50 particle size is 6.5μm.

[0055] Compatibilizer: ternary random copolymer of styrene-acrylonitrile-glycidyl methacrylate, SAG-005, Jiayirong Compatibilizer Jiangsu Co., Ltd.;

[0056] Phase change microcapsule 1#: phase change material is paraffin, wall material is melamine formaldehyde resin, XR-XB28-HA, Hefei Ruixue New Materials Technology Co., Ltd., phase change at 28℃;

[0057] Phase change microcapsule 2#: phase change material is butyl stearate, wall material is cross-linked polyurethane, phase change material FSM-PCM98, Fussman Technology (Beijing) Co., Ltd., phase change at 25°C;

[0058] Phase change microcapsule 3#: The phase change material is a paraffin-containing composite, the wall material is melamine formaldehyde resin, XR-XB42-HA, Hefei Ruixue New Material Technology Co., Ltd., 42℃ phase change.

[0059] Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, commercially available.

[0060] Lubricant: polysiloxane, GT-630, Zhejiang Jiahua Jinghua Co., Ltd.

[0061] The preparation method of the ABS composition of the following examples or comparative examples comprises the following steps: uniformly mixing the raw material components of the formula amount by a low-speed mixing device at a rotation speed of 175 rpm; and melt-blending and extruding by a twin-screw extruder to obtain the ABS composition. The temperature of the first and second zones of the twin-screw extruder is 155°C, the temperature of the third to fifth zones is 220°C, the temperature of the fifth to tenth zones is 220°C, and the screw speed is 300 rpm.

[0062] Examples 1 to 12

[0063] This embodiment provides a series of ABS compositions, and the raw material components thereof are shown in Table 1 in parts by mass.

[0064] Table 1

[0065]

[0066]

[0067] Comparative Examples 1 to 9

[0068] This comparative example provides a series of ABS compositions, and the raw material components thereof are shown in Table 2 in parts by mass.

[0069] Table 2

[0070]

[0071] Performance Testing

[0072] The ABS compositions of Examples 1-12 and Comparative Examples 1-9 were subjected to the following tests, and the results are shown in Table 3:

[0073] Notched impact strength: tested in accordance with ISO 180-2023 standard, notch type is A;

[0074] Thermal conductivity: tested in accordance with ISO 22007-2-2015 standard;

[0075] Insertion force retention rate after 30,000 insertions and removals: Injection molded into a medium-particle building block brick with 2×2 bosses (30mm×30mm×25mm), use an insertion force tester to continuously insert and remove 30,000 times, and test the insertion force retention rate at the 30,000th time;

[0076] Antibacterial performance: The sample of Example 1 was tested according to ISO 22196:2011 standard, and the bacterial species were Escherichia coli and Staphylococcus aureus. The results showed that the 24-hour antibacterial rate reached more than 98.5%.

[0077] Table 3

[0078]

[0079]

[0080] As can be seen from Table 3, the notched impact strength of the ABS composition of the present invention is 16.6 KJ / m 2 The thermal conductivity is above 0.29W / (m*K), the plugging and unplugging force retention rate is above 84.6% after 30,000 times, and the 24-hour antibacterial rate is above 93.3%. It has excellent toughness, long-term plugging and unplugging resistance and antibacterial properties.

[0081] Compared with Example 1, when the thermal conductive agent in Example 1 is too little, the thermal conductivity is low and the retention rate of the insertion and extraction force after 30,000 times is significantly reduced; when the thermal conductive agent in Example 2 is too much, the compatibility is poor, resulting in a significant decrease in the notched impact strength.

[0082] Compared with Example 1, Comparative Example 3 does not contain phase change microcapsules, and its 30,000 insertion and extraction force retention rate is significantly reduced; when the phase change microcapsules in Comparative Example 4 are excessive, the notched impact strength is reduced.

[0083] Compared with Example 1, when PET is not added in Comparative Example 5, it is not conducive to the enrichment of phase change capsules on the product surface, resulting in a decrease in the insertion and extraction force retention rate; when PET is excessive in Comparative Example 6, the toughness of the material is significantly reduced, and the notched impact strength is low. The intrinsic viscosity of PET in Comparative Example 7 is too low, which will lead to poor toughness and a significant decrease in notched impact strength; the intrinsic viscosity of PET in Comparative Example 8 is too high, and the compatibility with ABS resin is reduced, and the notched impact strength is reduced. The phase change point of the phase change microcapsules in Comparative Example 9 is too high, and the friction temperature rise during continuous insertion and extraction is large, resulting in a decrease in the insertion and extraction force retention rate of 30,000 times.

[0084] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An ABS composition, characterized in that: The composition includes the following components in parts by weight: The phase change point of the phase change microcapsule is 25-30°C; The intrinsic viscosity of the PET resin is 0.6-0.9 dL / g.

2. The ABS composition according to claim 1, characterized in that: The capsule wall material of the phase change microcapsule is melamine resin.

3. The ABS composition according to claim 1, characterized in that: The mass fraction of acrylonitrile monomer in the SAN resin is 22-28%.

4. The ABS composition according to claim 1 or 3, characterized in that: The SAN resin has a melt mass flow rate of 20-40 g / 10 min at a temperature of 220° C. and a load of 10 kg. The melt mass flow rate is measured according to ISO 1133 standard.

5. The ABS composition according to claim 1, characterized in that: The mass fraction of butadiene monomer in the ABS toughening agent is 60-65%.

6. The ABS composition according to claim 1, characterized in that: The PET resin is post-consumer recycled PET plastic.

7. The ABS composition according to claim 1, characterized in that: The compatibilizer is styrene-acrylonitrile-glycidyl methacrylate and / or styrene-acrylonitrile-maleic anhydride copolymer.

8. The ABS composition according to claim 1, characterized in that: The thermal conductor is one or more of zinc oxide, magnesium oxide or aluminum oxide.

9. A method for preparing the ABS composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing the raw material components in the formula, melting and blending and extruding the components at a processing temperature of 150-240° C., so as to obtain the ABS composition.

10. Use of the ABS composition according to any one of claims 1 to 8 in preparing building block toys.

Citation Information

Patent Citations

  • Halogen-free flame-retardant ABS / PET alloy and preparation method thereof

    CN101857712A

  • Preparation method of temperature-resistant ABS plastic

    CN111440412A

  • ABS / polyester alloy composition and a preparation method therefor

    WO2021135570A1